2022
DOI: 10.48550/arxiv.2203.01347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling X-shaped Radio Galaxies: Dynamical and Emission Signatures from the Back-flow model

Gourab Giri,
Bhargav Vaidya,
Paola Rossi
et al.

Abstract: Context. Active galactic nuclei typically show the presence of radio jets ranging from sub-kpc to Mpc scales. Some of these radio galaxies show distortion in their jets, forming tailed or winged sources. X-shaped radio galaxies are a subclass of winged sources formation mechanism of which is still unclear. Aims. The focus of this work is to understand hydro-dynamical back-flows and their role in dynamics and non-thermal emission signatures (in presence of radiative losses and diffusive shock acceleration) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The simulations of Giri et al (2022) also predict that the turbulent nature of the plasma in wings or diffuse tails will induce in situ re-energisation of particles through local shocks, causing the wing material to survive over longer time scales than what would be expected under a model of only radiative and adiabatic losses. More sensitive observations at high resolution at frequencies greater than 1 GHz that would detect the tails will allow for a highly resolved spectral analysis of the diffuse tails to confirm this scenario, for the case of 3C 34.…”
Section: Nature and Origin Of The Oldest Lobe Plasma: Filaments Scyth...mentioning
confidence: 96%
See 1 more Smart Citation
“…The simulations of Giri et al (2022) also predict that the turbulent nature of the plasma in wings or diffuse tails will induce in situ re-energisation of particles through local shocks, causing the wing material to survive over longer time scales than what would be expected under a model of only radiative and adiabatic losses. More sensitive observations at high resolution at frequencies greater than 1 GHz that would detect the tails will allow for a highly resolved spectral analysis of the diffuse tails to confirm this scenario, for the case of 3C 34.…”
Section: Nature and Origin Of The Oldest Lobe Plasma: Filaments Scyth...mentioning
confidence: 96%
“…We prefer the explanation given by Capetti et al (2002), who found a striking correlation between the axes of wings and those of host galaxies of radio sources -the wings are preferentially directed along the minor axis of their elliptical host galaxies, and there is a preference towards high projected ellipticity. This naturally allows the backflow to expand laterally due to the steeper pressure gradient in the ICM perpendicular to the jet axis, and has been modelled with numerical simulations (Leahy & Williams 1984;Capetti et al 2002;Giri et al 2022). The HST image in Figure 1 does not conclusively show an elliptical morphology but rather a spheroidal morphology for the host, which McCarthy et al (1995) attribute to a superposition of cluster members in the line of sight.…”
Section: Nature and Origin Of The Oldest Lobe Plasma: Filaments Scyth...mentioning
confidence: 99%
“…X-shaped sources are the opposite of DDRGs, in the sense that the active jets drive at a large angle from the axis of the more diffuse and older lobe plasma. It is not known whether X-shaped and 'winged' sources are truly restarting, as competing models exist for their formation (e.g., large deflection of their back-flow [270][271][272][273]) and as X-shaped sources of the LERG type (which are common in DDRGs) are rare. It should be noted that the formation of X-shaped lobes and restarted activity are not necessarily mutually exclusive, as the source PKS 2014-55 is known to have X-shaped lobes while being a DDRG [274]; thus, it is possible that X-shaped sources are truly a result of deflected backflows rather than restarted jets at a different angle.…”
Section: Jet Disruption Morphology and Accretion Ratementioning
confidence: 99%